Optimasi dan Uji Mutu Fisik Face Mist Rebusan Simplisia Daun Tapak Liman (Elephantopus Scaber) Sebagai Antioksidan dengan Menggunakan Metode Simplex Lettice Design: Penelitian - Bryan Dwi Multi; Anna Fitriawati; Septian Maulid W (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
One way to protect the skin from damage caused by free radicals is to increase antioxidant intake. The tapak liman plant (Elephantopus scaber) is one of the plants that has a very high flavonoid compound content that is effective as an antioxidant. One of the cosmetic preparations used to the face is face mist. The purpose of this study was to determine the antioxidant activity of the face mist preparation of boiled tapak liman leaves. This study was conducted by making a simple leaf of tapak liman (Elephantopus scaber) then continued with the manufacture of face mist preparations and optimization of glycerin and propylene glycol. The method used to obtain the optimum formula is the simplex lettice design method. The physical quality tests of the preparations carried out were homogeneity test, pH test, irritation test, spray power test, organoleptic test and drying time test. Antioxidant test with DPPH solution on the face mist preparation of boiled simple leaf of tapak liman (Elephantopus scaber). The results of the study obtained an optimum formula with a concentration of 20% glycerin and 10% propyleneglycol. The antioxidant activity of the optimum formula of the face mist preparation of the boiled simplicia of the tapak liman leaves (Elephantopus scaber) obtained an IC50 value of 129.525 ppm.